EFFECTS OF CLIMATIC AND GEOLOGICAL PROCESSES DURING THE PLEISTOCENE ON THE EVOLUTIONARY HISTORY OF THE NORTHERN CAVEFISH, AMBLYOPSIS SPELAEA (TELEOSTEI: AMBLYOPSIDAE). (20th December 2012) - Niemiller, Matthew L.; McCandless, James R.; Reynolds, R. Graham; Caddle, James; Near, Thomas J.; Tillquist, Christopher R.; Pearson, William D.; Fitzpatrick, Benjamin M.
<x xml:space="preserve">Abstract</x> Climatic and geological processes associated with glaciation cycles during the Pleistocene have been implicated in influencing patterns of genetic variation and promoting speciation of temperate flora and fauna. However, determining the factors promoting divergence and speciation is often difficult in many groups because of our limited understanding of potential vicariant barriers and connectivity between populations. Pleistocene glacial cycles are thought to have significantly influenced the distribution and diversity of subterranean invertebrates; however, impacts on subterranean aquatic vertebrates are less clear. We employed several hypothesis‐driven approaches to assess the impacts of Pleistocene climatic and geological changes on the Northern Cavefish, Amblyopsis spelaea, whose current distribution occurs near the southern extent of glacial advances in North America. Our results show that the modern Ohio River has been a significant barrier to dispersal and is correlated with patterns of genetic divergence. We infer that populations were isolated in two refugia located north and south of the Ohio River during the most recent two glacial cycles with evidence of demographic expansion in the northern isolate. Finally, we conclude that climatic and geological processes have resulted in the formation of cryptic forms and advocate recognition of two distinct phylogenetic lineages currently recognized as A. spelaea.